Antioxidant Activity Test Of Red Spinach Leaf (Amaranthus Tricolor L.) Extract And Fraction With Methode (2,2-Diphenyl-1 Picrylhydrazyl) - Khairunnisa, Anita; Noviyanti; Asterina, Yolanda (SPECTA Journal of Technology, 2025)
Abstract Red spinach (Amaranthus tricolor L.) is a leafy vegetable known for its high antioxidant potential due to its bioactive compounds. This study aimed to evaluate the antioxidant activity of extracts and fractions of red spinach leaves using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Extraction was conducted through cold maceration with ethanol 96%, followed by fractionation using solvents of varying polarity: n-hexane, ethyl acetate, and water. Phytochemical screening revealed the presence of alkaloids, flavonoids, quinones, saponins, steroids, and tannins, which contribute to the plant's antioxidant properties. The antioxidant activity of the ethanol extract and fractions was assessed based on their IC50 values. The ethanol extract demonstrated moderate antioxidant activity with an IC50 of 122.09 µg/mL, while the n-hexane and water fractions showed similar moderate activity with IC50 values of 117.33 µg/mL and 124.36 µg/mL, respectively. The ethyl acetate fraction exhibited strong antioxidant activity with an IC50 value of 64.77 µg/mL, attributed to the presence of semi-polar compounds such as flavonols. The results confirmed the significant free radical scavenging potential of red spinach, particularly in its ethyl acetate fraction. This study highlights the potential of red spinach leaves as a natural source of antioxidants with applications in the pharmaceutical, health, and food industries. Keywords: Red spinach, Amaranthus tricolor L., DPPH, antioxidant activity, IC50.